Risk Factors on the Incidence and Prognostic Effects of Colorectal Cancer With Brain Metastasis: A SEER-Based Study - Chen, Quan; He, Le; Li, Yuhong; Zuo, Chenghai; Li, Mengxia; Wu, Xiaofeng; Pu, Chengxiu; Xu, Xiang; Tang, Rongrui; Xiong, Yanli; Li, Juan (Frontiers in Oncology, 2022)
Background: Colorectal cancer (CRC) with brain metastases (BM) are an uncommon and at a late stage. The purpose of this study was to identify the clinical factors that can influence the incidence of CRC patients with BM (CRCBM), and to investigate the impact of clinical factors and therapies on the outcomes of CRCBM. Methods: Between 2010 and 2018, patients with CRCBM were enrolled under the Surveillance, Epidemiology, and End Results (SEER) program. Multivariable logistic and Cox regression models were used to identify risk factors and prognostic factors of BM. Kaplan-Meier curve and Log-rank test were used to evaluate overall survival (OS) and tumor-specific survival (CSS) of CRCBM patients. Results: A total of 195 (0.34%) CRC patients initially diagnosed with BM were included for analysis. The positive level of CEA, pN2a-b, or additional organs metastases were positively associated with developing BM from the CRC cohort (P < 0.05). The median OS and CSS of the BM patients were both 4.0 months, while the corresponding survival time in CRC patients without BM was 14.0 and 16.0 months, respectively (HR= 2.621, 95% CI=2.061-3.333 for CSS; HR=2.556, 95% CI=2.026-3.225 for OS; log rank P<0.001, each). Only systematic treatment was independently associated with the better survival (P < 0.05, each). Conclusions: Although the overall prognosis of CRCBM patients was extremely poor, the positive level of CEA, pN2a-b and distant metastases could be bad risk factors for the incidence of CRCBM. In addition, only systematic treatment was found to be a negative prognosis factor for CRCBM patients. These related factors can provide more valuable reference for clinical individualized treatments.